STUDY OF FACTORS RESPONSIBLE FOR FAILURE OF INDUCTION OF LABOR IN TERM NULLIPAROUS WOMEN - Hantodkar, Monika (Journal of Biomedical and Pharmaceutical Research, 2020)
BACKGROUND: Worldwide, unsuccessful induction of labor is a public health concern. The unfavorable outcome of an emergency cesarean section is increased when labor induction attempts fail, and this is linked to an increased rate of morbidity in both the mother and the fetus. Additionally, it raises the possibility of a number of unfavorable outcomes for both the mother and the unborn child, including uterine rupture, unsettling fetal heart rate tracing, postpartum hemorrhage, stillbirth, and severe delivery asphyxia. Healthcare costs and maternal and newborn outcomes are impacted by unsuccessful labor induction, particularly in low-resource settings where the incidence of labor induction is low but the prevalence of failure induction is higher. One aspect of comprehensive obstetric care services that is being used more frequently in modern obstetrics to lower the risk of morbidity and mortality among mothers and newborns is induction of labor. AIM: The purpose of the study was to evaluate the contributing factors to unsuccessful hospital inductions of labor (IOLs). MATERIAL AND METHOD: This cross-sectional investigation was done in the gynecology department. The entire study population consisted of 200 patients, 48 of whom had a CS and 152 of whom had a vaginal birth. Patients were split into two groups based on delivery mode: Group A (vaginal delivery) and Group B (CS). With the aid of long artery forceps and aseptic procedures, the patient was maintained in the lithotomy position while an intracervical Foley catheter 22-24 gauge was put under direct eyesight through Sim’s speculum. A maximum of 50 milliliters of distilled water were pumped into the catheter’s balloon. Prostaglandin E2 (PGE2) 3mg was inserted vaginally after 10–12 hours of foley’s catheter placement, and the dose was repeated after 6 hours. RESULTS: The entire study population consisted of 200 patients, 48 of whom had a CS and 152 of whom had a vaginal birth. While mild preeclampsia was more significant in Group B, gestational diabetes was more prevalent in Group A. Following multinomial logistic regression analysis, patients with moderate preeclampsia had a threefold increased risk of developing CS. Throughout the entire study population, the average PGE dosage was 2.12 (±1.03) mg. Nevertheless, it was greater in the patients who had CS when taking into account the mode of delivery. The PGE dose was higher for individuals who delivered delivery vaginally only in the "preeclampsia" subgroup. CONCLUSION: Our results are particularly intriguing because the success rate was high even though we chose a group of patients who were at risk of not succeeding with labor induction. Thus, clinical problems including maternal diabetes, hypertension, isolated oligohydramnios, and PROM, as well as parameters like "nulliparity," "gestational age," "unfavorable Bishop score," and "kind of used dinoprostone," do not individually affect the induction success. Then, in order to prevent needless CS, a number of maternal and fetal factors that affect the success of labor induction must be considered. As such, inducing labor is a highly responsible medical procedure that necessitates a comprehensive evaluation of the mother’s and fetus’s health. KEYWORDS: Labor induction; Caesarean section; Failed induction and Associated factors